1983
DOI: 10.1002/app.1983.070281002
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between the thermal properties of modified polyurethane elastomers and the efficiency of antipyrens

Abstract: SynopsisA study is made of the relationship between the thermal properties of polyurethane elastomers and the efficiencies of antipyrens containing phosphorus and some containing both phosphorus and chlorine. It is shown that a relationship exists between the thermal properties of polyurethane elastomers and the efficiencies of the antipyrens. It is also found that the presence of antipyrens in the molecules of the polyurethane elastomer effects the course of DTA, DTG, and TG curves. This permits antipyren eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…With composition C 3, the CR is 2.5 times as much as that for the initial composition, and the exothermic area of exothermic peaks I and II is more than twice as low as for the untreated sample. As our previous studies ofPU elasomers showed [19], increase of the concentration of P above 1% does not lead to a substantial improvement in thermal behaviour. Thus~ the polymer is prevented from rapid heating and its decomposition shifts to higher temperatures.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…With composition C 3, the CR is 2.5 times as much as that for the initial composition, and the exothermic area of exothermic peaks I and II is more than twice as low as for the untreated sample. As our previous studies ofPU elasomers showed [19], increase of the concentration of P above 1% does not lead to a substantial improvement in thermal behaviour. Thus~ the polymer is prevented from rapid heating and its decomposition shifts to higher temperatures.…”
Section: Resultssupporting
confidence: 50%
“…The P found is in the form of P = O bonds (the adsorption band in the IR spectrum is at 1240 cm-1) [18] and it comprises more than 10% of the initial quantity. An increase in exothermic peak I and a decrease in thermostability was established for Cl-contai'ning polyurethane elastomers [19], suggesting a change in the polymer structure at Cl-containing antipyrene concentrations higher than the optimum. In this case it is possible for C!…”
Section: Resultsmentioning
confidence: 95%
“…With MPUE-P the first exothermal peak is greatly reduced and shifted towards higher temperatures (Fig. Further, it was established ( Table 1) that with samples containing the optimum concentration of antipyrene [8] the Eef values are higher than those for IPUE and the other MPUE-P. On the other hand, the I R spectra (Fig.…”
Section: Thermal Destruction Of Mpue-pmentioning
confidence: 87%
“…In an earlier work [8] on the same polyurethane elastomers (PUE) modified with phosphorus and phosphorus/chlorine, a connection was found between their thermal behaviour (shift and intensity reduction of the first thermal peak) and the value of the oxygen index. This correlation gives information on the optimum concentration of antipyrene as concerns its effectiveness for combustion retardation.…”
mentioning
confidence: 93%